Computationally Investigate Low Velocity Hydrokinetic Turbines with Variant Systems - P. P. Gohil; V. Patel; A. U. Mehta (Journal of Applied Fluid Mechanics)
A high velocity is rarely accessible in water streams such as rivers, canals, and outlets of sewage and common effluent treatment plants. However, an average velocity of 0.5 - 1.0 m/s is reported to be available in many water streams most of the time. Hydrokinetic (HK) turbines can extract power from the flowing water in these streams. Considering the small quantum of power generated, the economic factor is more significant than efficiency. A Savonius-type HK turbine can generate energy from low-velocity magnitudes of around 0.5 m/s, although it remains a low-speed and low-efficiency turbine. In this study, an attempt has been made to computationally investigate the performance of the Savonius turbine in a water stream channel. It is observed that the performance of the Savonius turbine is not significant, and the generated power cannot be utilized constructively for different applications. Therefore, it is necessary to develop and investigate variant constructive systems to enhance turbine performance. This manuscript focuses on exploring these variant systems and understanding their performance characteristics. Four variant systems have been selected: (i) System-1: Solely Savonius turbine, (ii) System-2: Savonius turbine with a flume, (iii) System-3: Deflector section used before the flume, and (iv) System-4: Deflector section used before the turbine. The investigation was carried out for these four variant systems using the Fluent commercial code. The results indicate that the Coefficient of performance (Cp) is low for System-1, solely Savonius turbine, with a value of 0.052. For the other variants, Cp values were found to be 0.357, 1.385, and 0.579 for the turbine with a flume, deflector before the flume, and deflector before the turbine respectively at the Tip Speed Ratio (TSR) is 1. Moreover, the study also extends to optimizing Cp under different TSR for the different variant systems. The intention is to use this study to install an HK turbine with an optimum constructive structure for maximizing and stabilizing the power that can be used for an isolated application.